Evaluation of Circular Buffer and Service Area Buffer Methods in Accessibility Analysis of Trans Metro Bandung Route 1 Based on GIS - Adibah, Fairuz; Saputra, Doddy Cahyadi; Sugasta, Hervian Handika; Parabi, Ashraf Dhowian; Santosa, Dimas Puji (Fakultas Teknik Universitas Tanjungpura, 2025)
This study examines public transportation accessibility in Bandung, the capital of West Java Province, located at 107 °36' E and 6 °55' S, covering 167.31 square kilometers and characterized by a mountainous